2007
DOI: 10.1021/bi062177x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM1-Mediated Amyloid-beta Fibrillogenesis and Membrane Disruption

Abstract: There is increasing evidence that a class of cell membrane glycolipids, gangliosides, can mediate the fibrillogenesis and toxicity of Alzheimer's disease amyloid-beta peptide (Abeta). Using lipid monolayers and vesicles as model membranes, we measured the insertion of Abeta into 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC)-ganglioside GM1 monolayers to probe Abeta-GM1 interactions, imaged the effects of Abeta insertion on monolayer morphology, and measured the rate of Abeta fibril formation when incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
83
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 48 publications
(85 reference statements)
10
83
0
11
Order By: Relevance
“…During incubation with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine vesicles containing physiological levels of GM1, the association of Ab with vesicles seeds the formation of Ab fibrils. Thus, favorable interactions between Ab and GM1 in the cell membrane provide a mechanism for Ab fibrillogenesis in vivo, and Ab-induced disruption of the cell membrane may provide a pathway by which Ab exerts toxicity (61).…”
Section: Interaction Of Abs With Gangliosidesmentioning
confidence: 99%
“…During incubation with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine vesicles containing physiological levels of GM1, the association of Ab with vesicles seeds the formation of Ab fibrils. Thus, favorable interactions between Ab and GM1 in the cell membrane provide a mechanism for Ab fibrillogenesis in vivo, and Ab-induced disruption of the cell membrane may provide a pathway by which Ab exerts toxicity (61).…”
Section: Interaction Of Abs With Gangliosidesmentioning
confidence: 99%
“…Indeed, several studies have visualized extensive A␤ association with cell and synthetic membranes (9,10). These surfaces have been shown either to increase the degree of amyloid fibril formation or to inhibit the process, based on the charge, curvature, and composition of the lipid surface (11)(12)(13)(14). Given that the composition of the surface has a significant impact on the self-association and aggregation of A␤, it is highly likely that individual lipid molecules can also impact on these processes.…”
mentioning
confidence: 99%
“…Indeed, a number of studies have shown that Aβ is able to perturb lipid bilayers (Arispe et al, 1993). Interest in studies of the interaction between Aβ and constituents of brain membranes has been further stimulated by the identification of an Aβ-GM1 ganglioside-bound form in AD brain (Chi et al, 2007; Kakio et al, 2002;Yanagisawa et al, 1995). …”
mentioning
confidence: 99%